Patterns and trends of Computed Tomography usage among pediatric and young adult patients in a private hospital in Rio de Janeiro, 2005-2015 (Brazilian Journal of Radiation Sciences, 2018)
Computed tomography (CT) scanning is a relatively high-dose procedure which use has been rapidly increasing in many countries, although a decline has been observed recently in some developed countries. Relatively little is known about CT usage in Brazil. A recent report showed that number of CT procedures among outpatients of the Brazilian public healthcare system (SUS) tripled from 2001 to 2011 and about 13% of all CTs procedures were underwent among pediatric and young adult patients. In the present study, we aimed to evaluate CT use in the private healthcare system, where the larger availability of CT scanners may result in a different CT usage pattern. We evaluated data from 15,892 CT procedures underwent by children and young adults (